Equilibria of l,l,2-Trichloro-l,2,2-trifluoroethane on Activated Carbons - Cho, S.Y.; Lee, Y.Y. (1995)
ChloroFluoroCarbons (CFCs) are now considered to be the prime contribution to stratospheric ozone depletion. As a result, the use of activated carbons to adsorb specific CFCs has received great attention. In this paper, the equilibrium adsorption characteristics of 1,1,2-trichloro-1,2,2-trifluoroethane vapor on different-shaped carbons were studied. Adsorption isotherms of 1,1,2-trichloro-1,2,2-trifluoroethane on an activated carbon pellet and an activated carbon felt were measured. The equilibria of 1,1,2-trichloro-1,2,2-trifluoroethane on the activated carbon pellet having a dual pore structure were expressed by the Redlich-Peterson equation, and equilibrium constants were expressed as functions of temperature from 298 to 393 K. On the other hand, the equilibria of 1,1,2-trichloro-2-trifluoroethane on the activated carbon felt having a relatively uniform pore structure were interpreted by the Dubinin-Radushkevich correlation based on the micropore volume filling theory. The affinity coefficient was correlated by the molar polarization. ？ 1995, American Chemical Society. All rights reserved.
Keywords: Activated carbon; Adsorption; Adsorption isotherms; Porosity; Pressure measurement; Pressure transducers; Refractive index; Surface measurement; Vapors; Activated carbon felt; Activated carbon pellet; Adsorption equilibria; Micropore volume filling theory; Redlich Peterson equation; Surface area; Chlorofluorocarbons; Activated Carbon; Adsorption; CFCs